Development of Tc99m-N4-NIM for Molecular Imaging of Tumor Hypoxia. (10th June 2012) - Ali, Mohammad S.; Kong, Fan-Lin; Rollo, Alex; Mendez, Richard; Kohanim, Saady; Smith, Daniel Lee; Yang, David J.
Abstract : The nitro group of 2-nitroimidazole (NIM) enters the tumor cells and is bioreductively activated and fixed in the hypoxia cells. 1, 4, 8, 11-tetraazacyclotetradecane (N4) has shown to be a stable chelator forT c 99 m . The present study was aimed to developT c 99 m -cyclam-2-nitroimidazole (T c 99 m -N4-NIM) for tumor hypoxia imaging. N4-NIM precursor was synthesized by reacting N4-oxalate and 1, 3-dibromopropane-NIM, yielded 14% (total synthesis). Cell uptake ofT c 99 m -N4-NIM andT c 99 m -N4 was obtained in 13762 rat mammary tumor cells and mesothelioma cells in 6-well plates. Tissue distribution ofT c 99 m -N4-NIM was evaluated in breast-tumor-bearing rats at 0.5–4 hrs. Tumor oxygen tension was measured using an oxygen probe. Planar imaging was performed in the tumor-bearing rat and rabbit models. Radiochemical purity ofT c 99 m -N4-NIM was >96% by HPLC. Cell uptake ofT c 99 m -N4-NIM was higher thanT c 99 m -N4 in both cell lines. Biodistribution ofT c 99 m -N4-NIM showed increased tumor-to-blood and tumor-to-muscle count density ratios as a function of time. Oxygen tension in tumor tissue was 6–10 mmHg compared to 40–50 mmHg in normal muscle tissue. Planar imaging studies confirmed that the tumors could be visualized clearly withT c 99 m -N4-NIM in animal models. Efficient synthesis of N4-NIM was achieved.T c 99 m -N4-NIM is a novel hypoxic probe and may be useful in evaluating cancer therapy.